Early lexical processing of Chinese one-character words and Mongolian words: A comparative study using event-related potentials - Zhang, Kai; Gu, Feng; Yu, Hongzhi (Frontiers in Psychology, 2023)
Logographic language and alphabetic language differ significantly in orthography. Investigating the commonality and particularity of visual word recognition between the two distinct writing systems is informative for understating the neural mechanisms underlying visual word recognition. In the present study, we compared the chronometry of early lexical processing and the brain regions involved in early lexical processing between Chinese (logographic language) and Mongolian (alphabetic language) by recording event-related potentials (ERPs) using both implicit and explicit reading tasks. Familiar Chinese one-character words (lexical) and unknown Chinese one-character words (non-lexical) were pseudorandomly presented to native Chinese readers in Experiment 1. Mongolian words (lexical) and pseudowords (non-lexical) were pseudorandomly presented to native Mongolian readers in Experiment 2. In the color decision task, participants were asked to decide the color (black or blue) of each stimulus. In the lexical recognition task, participants were asked to report whether they could recognize each stimulus. The results showed that in both experiments and both tasks, ERPs to lexical items differed significantly from those to non-lexical items in the parietooccipital scalp region approximately 250 ms after stimulus onset, reflecting the early lexical processing, which likely originated from the ventral occipitotemporal cortex as revealed by source analysis. These results indicated that although Chinese and Mongolian differed markedly in orthographic features, the neural mechanisms underlying early lexical processing are similar between the two languages.